Day 2 Tue, October 22, 2019 2019
DOI: 10.2118/198651-ms
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a New Eco-Friendly Drilling Fluid Additive to Enhance the Filtration Properties of Water-Based Drilling Fluid Systems

Abstract: The main objective of this paper is to develop a new material used to control the seepage losses and combat issues regarding thick mud cake. The plan is to develop a biodegradable waste material from Grass, which is environmentally friendly to be utilized as an alternative material to address filtration problems. Raw material from local Grass in the USA was used to construct the fibrous fluid loss control agent (Grass Powder). The lab procedure consisted of crushing and grinding process to assemble the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Tere exist several classifcations of both natural and modifed polymers that are used in drilling fuids, serving to improve the rheological characteristics and boost the efcacy of well-cleaning operations [5]. Natural polymers (biopolymers), such as starch [112], quebracho [113], xanthan gum [114], guar gum [115], welan gum [116][117][118], scleroglucan [118], locust bean gum [119,120], and lignosulfonates [121,122] are considered very suitable. However,…”
Section: Well-cleaning Capabilities Associated With Naturalmentioning
confidence: 99%
“…Tere exist several classifcations of both natural and modifed polymers that are used in drilling fuids, serving to improve the rheological characteristics and boost the efcacy of well-cleaning operations [5]. Natural polymers (biopolymers), such as starch [112], quebracho [113], xanthan gum [114], guar gum [115], welan gum [116][117][118], scleroglucan [118], locust bean gum [119,120], and lignosulfonates [121,122] are considered very suitable. However,…”
Section: Well-cleaning Capabilities Associated With Naturalmentioning
confidence: 99%
“…In addition, Al-Hameedi et al found that biodegradable grass powder (GP) in comparison to starch, which is a commonly used additive, was batter able to control fluid circulation loss. Although starch showed better rheological properties than GP, this indicates that grass can be used in a supporting capacity in combination with starch to provide a more environmentally friendly additive [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another research was also done by Omotioma, et al [7] and they found out that cashew and mango leaves extract improved rheological properties in water based mud because it showed suitable results as mud additives. Of the two plants, mango showed higher improvement than cashew nut [8]. Found out that cellulose from ground nuts shells could do better than polyanionic cellulose (PAC) when used to formulate the drilling mud.…”
Section: Introductionmentioning
confidence: 99%